Descriptors for competence : towards an international standard classification for skills and competences - Markowitsch, Jörg [Verfasser]; Plaimauer, Claudia [Verfasser] (My University, 2009)
"The purpose of this paper is to investigate the potential of already existing skills and competence ontologies to benefit European transparency tools and especially the implementation of the European Qualification Framework. Furthermore, it asks whether any of them could serve as a starting point to develop an International Standard Classification of Skills and Competences to supplement ISCED and ISCO." The contribution contains a comparative analyses of three systems providing ontologies of skills and competences: DISCO, O*NET and Taxonomy_DB. "The analysis identifies O*NET as the most promising candidate to serve European transparency instruments and the EQF. Furthermore, it demonstrates that the development of an International Standard Classification of Skills and Competences, that is suitable for statistical purposes as well as appropriate for practical applications in human resource management and in the area of education, would have to integrate very diverging demands, which so far are being best met by O*NET and DISCO." (Autorenreferat, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Europäischer Qualifikationsrahmen; Kompetenz; Klassifikation; Österreich